2021
DOI: 10.3897/rio.7.e63872
|View full text |Cite
|
Sign up to set email alerts
|

Open comments on the Task Force SIRS report: Scholarly Infrastructures for Research Software (EOSC Executive Board, EOSCArchitecture)

Abstract: The goal of this document is to openly contribute with our comments to the EOSCArchitecture report: Scholarly Infrastructures for Research Software (SIRS), and thus, to participate in the European Open Science Cloud (EOSC) architecture design.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 10 publications
0
12
0
Order By: Relevance
“…In this section we bring together some of the existing definitions of software as a legal object (see references below). We also recall our definition of RS coming from 3 , 18 .…”
Section: Research Softwarementioning
confidence: 99%
See 4 more Smart Citations
“…In this section we bring together some of the existing definitions of software as a legal object (see references below). We also recall our definition of RS coming from 3 , 18 .…”
Section: Research Softwarementioning
confidence: 99%
“…Beyond the vision of software as a legal object, we bring here the concept of Research Software (RS) as a scientific production, as defined in 3 , 18 : Research Software is a well identified set of code that has been written by a (again, well identified) research team. It is software that has been built and used to produce a result published or disseminated in some article or scientific contribution.…”
Section: Research Softwarementioning
confidence: 99%
See 3 more Smart Citations